Le rôle de la presse française dans la promotion du régime fiscal de « résident non habituel » portugais - Cécilia Brassier-Rodrigues; Françoise Cognard (Communiquer)
Since 2009, a status of “Non-Habitual Resident” (NHR) exists in Portugal. This, by introducing a number of tax benefits, has prompted the installation of European nationals in Portugal, and especially many French. The analysis of a corpus of 56 articles, published between May 2, 2013, and April 5, 2018, reveals how the French has interpreted this public policy, thus contributing to the promotion of migration to Portugal. We analyzed the particular aspects of international and intercultural communication developed by the national media around these new forms of migration, both heliotropic and economic.